Application of Polymer Nanocolloid Preparation in Stability Analysis of Motion Mechanics - Jun Jia; Fengyuan Sun (Advances in Materials Science and Engineering)
Nanomaterials are widely used in various fields because of their own advantages. When the particle size of the material is reduced to the nanometer level, it will lead to new characteristics of acoustic, optical, electrical, magnetic, and thermal properties. This will greatly enrich the research content of the material and is expected to get new uses. Therefore, the preparation technology of nanomaterials is one of the current research hotspots and has broad application prospects. At present, the most commonly used preparation techniques are hydrothermal method and sol-gel method, but not all crystals grow in a hydrothermal environment, so this paper adopts the sol-gel method for preparation. However, in the preparation of nanocolloids, agglomeration often occurs between colloidal nanoparticles. In order to avoid the agglomeration between particles, this paper adopts an appropriate method to disperse the particles. In order to further explore the stability of nanocolloids, the colloidal film material prepared by the cadmium sulfide (CdS) sol method was used as the research sample. It also proposes a sol preparation method incorporating ultrasonic waves and further discusses the kinetic characteristics. The research results show that the sedimentation velocity of 1 nm cadmium sulfide nanocolloids in water is 1.3 × 10−12 (m/s) prepared by colloid of cadmium sulfide.